Distribution and spatial autocorrelation of physical-water attributes of an Oxisol - Teixeira de Oliveira, Job; Alves de Oliveira, Rubens; Milena Rojas Plazas, Gloria; Moreira Andrade, Sinomar; França da Cunha, Fernando (Revista Brasileira de Engenharia de Biossistemas, 2023)
Spatial autocorrelation, which in this work was calculated using Moran's bivariate analysis, can be defined as the coincidence of similar values in nearby locations, or the absence of randomness of a variable due to its spatial distribution. Therefore, the objective of this study is to analyze the distribution and spatial autocorrelation of physical attributes of an Oxisol. The experiment was carried out in the irrigation and drainage area of the Universidade Federal de Viçosa, in Viçosa, Minas Gerais, Brazil. The soil in which the experimental meshes were installed was classified as a sandy clayey Oxisol. The attributes were determined: soil moisture on a dry basis, % (DB), soil moisture on a wet basis, % (WB), volumetric soil moisture, % (VS), particle density, g cm-1 (PD), sampled at different depths and within a grid of 90 georeferenced points. For spatial autocorrelation, the global Moran and local Moran indexes (LISA) were used as statistical tools. Bivariate analysis revealed that soil volumetric moisture is closely related to wet and dry basis moisture. It was also found that the surface particle density is related to the deeper layers of the soil, thus reinforcing that the solid fraction of a soil sample, without considering porosity, tends to remain constant. This happens because the predominant mineral constituents in soils are quartz, feldspars, and colloidal aluminum silicates, whose particle densities are around 2.65 g cm-3.